China and the Philosophy of Mutations (Devenires, 2013)
During the rule of the Song dynasty, centuries after the decline of Confucianism, China witnessed a revitalization of this philosophical tradition. Enriched with new cosmological and metaphysical elements borrowed from Buddhism and Daoism, the doctrine of Li of the Song and Ming periods, traditionally known in the West as Neo-Confucianism, came into being. Since the 11th century up to the present day, this system of thought has remained highly influential in China. The present article describes some of the fundamental elements of Neo-Confucianism such as taiji 太極, qi 氣, and li 理 and examines the ramifications of these and other concepts for scientific reasoning. The paper revisits Joseph Needham’s work in order to analyze some of the fundamental postulates of Chinese science: yin 陰 and yang 陽, the five elements or processes (wuxing 五行) as well as the contents of Yijing 易經 or The Book of Changes. The engagement with some of the controversial points surrounding the latter text, whose influence on Chinese thought throughout centuries cannot be underestimated, serves as a reference point for the analysis of causality and for the evaluation of the mystical content underlying much of traditional Chinese philosophy.